2015
DOI: 10.22146/ijc.21197
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization Superabsorbent Hydrogels of Partially Neutralized Acrylic Acid Prepared Using Gamma Irradiation; Swelling and Thermal Behavior

Abstract: A series of superabsorbent hydrogels were synthesized from partially neutralized acrylic acid with varying degree of neutralization (0-1) using gamma radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…It is indicated that the prepared homopolymer hydrogels with 0% and 100% of KOH resulted in a small amount of crosslinked hydrogel network. As a result, the hydrogel products can only absorb and retain small quantities of water [31].…”
Section: E Eds Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It is indicated that the prepared homopolymer hydrogels with 0% and 100% of KOH resulted in a small amount of crosslinked hydrogel network. As a result, the hydrogel products can only absorb and retain small quantities of water [31].…”
Section: E Eds Studymentioning
confidence: 99%
“…The radiation processing has several advantages such as the simultaneous crosslinking and sterilization in one step and the easy control of physical properties of hydrogels by combining dose with polymer composition; it allows fabricating a pure and human-friendly product noncontaminated with ballast materials or the residuals of toxic initiators [30]. Irradiation technique was successfully reported by some researchers to synthesize superabsorbent hydrogels, some were using gamma-irradiation [24], [25], [30], [31], blue and green LED irradiations [32], microwave irradiation [26], and electron beam irradiation [33]. The aim of this research is to synthesize the superabsorbent hydrogel from chitosan and partially neutralized the acrylic acid by using the gamma-irradiation method.…”
Section: Introductionmentioning
confidence: 99%
“…This results in negative charges along the repelling polymer chain, which forces the polymer chain to open and bind water with hydrogen bonds (Kalhapure et al, 2016). There is also an increase in the hydrogel porosity as water diffuses into the hydrogel pores (Erizal et al, 2015).…”
Section: Gel Fraction and Water Absorption Analysismentioning
confidence: 99%
“…Hidrogel berbasis asam akrilat menunjukkan sifat khusus dengan adanya asam karboksilat sebagai gugus samping anion dalam jaringannya. keberadaan gugus anion dalam asam akrilat dapat dilakukan dengan netralisasi gugus asam dalam fase cair (biasanya dengan natrium atau larutan kalium hidroksida), dan diikuti dengan pengikatan silang untuk polimerisasi [19].…”
Section: Pendahuluanunclassified